Determination of stock in inbound logistics based on optimal order quantity through Smart Application for Chicken Egg Stock (SAFCES) - Hidayat, Agung Prayudha; Santosa, Sesar Husen; Siskandar, Ridwan; Dardanella, Derry; Ferdinant, Putro Ferro (Universitas Sultan Ageng Tirtayasa, 2025)
Ensuring a stable supply of chicken eggs to meet fluctuating market demand is essential for maintaining market stability and trader profitability. To address this challenge, the Smart Application for Chicken Egg Stock (SAFCES) was developed to optimize storage capacity for chicken eggs, extending beyond the traditional focus on determining order quantities. By employing a fuzzy logic approach, SAFCES accurately calculates the optimal order quantity and establishes minimum and maximum stock levels (Min-Max) to ensure consistent maintenance of ideal storage capacity. This innovative application enhances decision-making by providing traders with real-time insights into stock requirements, enabling them to adapt swiftly to demand variations. The implementation of SAFCES successfully supports traders in sustaining optimal stock levels, meeting both order and safety stock requirements, and keeping inventory within the desired thresholds. Furthermore, SAFCES promotes operational efficiency by reducing stockouts and overstocking, ultimately contributing to a more resilient supply chain for chicken eggs in dynamic market conditions.